Impact of discrete source step size on the 3D dosimetry of interstitial implants with high dose rate brachytherapy - Maurya, Anil Kumar; Maurya, Rajesh Kumar; Maurya, Surendrakumar Dayashankar; Kesarwani, Radha; Singh, Virendra (International Journal of Research in Medical Sciences, 2018)
ABSTRACT Background: High dose rate remote after loading brachytherapy machines have seen tremendous advancement both technologically and their clinical applications during the last 25 years. With the introduction of computerized remote after loading machines and computerized planning system, stepping source dosimetry system (SSDS) has become the system of choice making almost all traditional dosimetry systems obsolete. In this study we evaluated the impact of source step size on dosimetry of interstitial implant using parameters of ICRU-58 and various quality indices (QI). Material & Methods: For this study, 10 implant cases which have 3-D CT image based planning were selected. Contouring of clinical target volume and various organs were done following standard guidelines for the same. Plans were optimized to achieve the desired clinical outcome using different source step sizes of 2.5, 5 and 10 mm respectively. Cumulative DVH’s were calculated for the estimation of various ICRU-58 parameters and quality indices. Results and Conclusion: The mean values of the target volumes, minimum target doses, treated volumes, low dose volumes; high dose volumes, overdose volumes, reference volumes, coverage, external volume, relative dose homogeneity, overdose volume and COIN indices have been presented for the source step sizes of 2.5 mm, 5 mm and 10 mm respectively. Among source step sizes used in this study, most favorable clinically acceptable dose distributions & dose homogeneity occurs around step size of 5 mm as predicted by the various parameters of ICRU-58 and dose quality indices. Keywords: Brachytherapy, interstitial implant, source step-size, remote after loading, optimization, quality indices.